Pitfalls of stenting coarctation of an angulated right circumflex aortic arch in Goldenhar syndrome - Elaheh Malakan Rad; Hojjat Mortezaeian; Hamid Reza Pouraliakbar; Ziyad M Hijazi (Wolters Kluwer Medknow Publications, 2017)
We report stenting of coarctation of an angulated right circumflex aortic arch (RCAA) using four Cheatham Platinum stents in a child with Goldenhar syndrome. Difficulties in measuring the accurate length of the curved and narrowed transverse aortic arch marked discrepancy between the luminal diameters of the long narrow transverse arch and wide descending thoracic aorta, increased displacement force caused by the 90° bend between the two parts resulted in repeated stent migrations. We discuss the tips to avoid distal stent migration in the setting of an angulated RCAA.